Heavy Metal Resistance Genes Are Associated with bla(NDM-1)- and bla(CTX-M-15)-Carrying Enterobacteriaceae - Yang, Qiu E. (Antimicrob Agents Chemother, 2018)
The occurrence of heavy metal resistance genes in multiresistant Enterobacteriaceae possessing bla(NDM-1) or bla(CTX-M-15) genes was examined by PCR and pulsed-field gel electrophoresis with S1 nuclease. Compared with clinical susceptible isolates (10.0% to 30.0%), the pcoA, merA, silC, and arsA genes occurred with higher frequencies in bla(NDM-1)-positive (48.8% to 71.8%) and bla(CTX-M-15)-positive (19.4% to 52.8%) isolates, and they were mostly located on plasmids. Given the high association of metal resistance genes with multidrug-resistant Enterobacteriaceae, increased vigilance needs to be taken with the use of heavy metals in hospitals and the environment.